Development of cow cart tourism in palbapang: efforts to preserve culture and improve the economic welfare of local communities - Pinontoan, Nexen Alexandre; Nurbaeti, Nurbaeti; Boediman, Surya Fadjar (Jurnal Mantik, 2024)
Culture-based tourism has become a strategic sector in the development of the local economy, especially in regions with rich cultural heritage. In Palbapang, the cow cart tourism initiative was introduced as an effort to preserve culture and improve the local economy. This study uses a qualitative approach to explore the public's perception of tourism, with data collected through in-depth interviews and direct observations, and analyzed thematically. The results of the study show that cattle cart tourism in Palbapang has received a positive response from the community, tourism managers, and the local government, considered important in preserving local culture and supporting the economy through the involvement of Micro, Small, and Medium Enterprises (MSMEs). However, sustainability challenges remain, especially when it comes to managing negative impacts such as congestion and cleanliness, which requires strategic planning and collaboration between all stakeholders